Characterization of siliceous cake for the beneficiation of 231Pa. (April 2021) - Dalvi, Aditi A.; Remya Devi, P.S.; Singh, Vishal; Tewari, R.; Verma, R.; Swain, Kallola K.
Abstract: Siliceous cake, a waste from monazite processing plant at Aluva, Kerala, is a rich and natural source of protactinium ( 231 Pa). Protactinium was recovered from this source using oxalic acid as a leaching agent. Field Emission Scanning Electron Microscopy, Energy Dispersive Spectrometry, Energy Dispersive X-ray Fluorescence and gamma spectrometry were utilized for the analysis of streams of the hydrometallurgical process for beneficiation of 231 Pa from siliceous cake. Field emission scanning electron microscope equipped with energy dispersive spectrometer was used to assess morphology, particle size, and elemental composition. The results were helpful to understand the effects of these parameters on the leaching of 231 Pa. X-ray and gamma ray spectrometric measurements were carried out to determine inactive elements and radionuclides present in the samples, respectively. The data gave an insight into the chemistry of the recovery process for 231 Pa and also helped in optimizing the experimental procedure to improve the efficiency of the leaching process. It also gave information about the elements/radionuclides accompanying 231 Pa during its recovery from the source material which will help in devising a procedure for its purification. Graphical abstract: Image 1 Highlights: Oxalic acid used as leaching agent for beneficiation of 231Pa from siliceous cake, waste product of monazite processing plant. FESEM, EDS, EDXRF and gamma spectrometry were used for characterization of materials of each stage of the process. Information regarding change in morphology, particle size, elemental and radionuclide composition was obtained at each stage. The results obtained were utilized to understand the chemistry involved at each stage of the beneficiation process. The information will help in devising an efficient separation procedure for purification of 231Pa from accompanying elements.